Shari'ah standard of business contract - Billah, Mohd. Ma'sum (A.S. Noordeen, 2006)
This study deals with the Shari'ah Standard of Business Contract. The introduction presents a general idea of the law of contract in Islam and its development and significance to human life. The study has been divided into four chapters and ending with final remarks.